2004
DOI: 10.1159/000078382
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q<sub>10</sub> Levels in Maternal Plasma and Cord Blood:Correlations with Mode of Delivery

Abstract: Background: Oxygen (O2) plays a critical role in the O2-reduction reactions indispensable for life, but can produce free radicals that are involved in many diseases. Coenzyme Q10 (CoQ10), acting as a redox carrier in the respiratory chain, occupies a central position in the energy metabolism and oxidative defence. Neonates seem to be very subjected to oxidative stress because of their deficient antioxidant systems. Design/Methods: The aim of the study was to verify w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…Our cord plasma samples being a mixture of arterial and venous cord plasma showed median TQ10 levels of 113 ng/mL and was in excellent agreement with levels found exclusively in venous cord plasma (mean, 112 ng/mL) [50], arterial (median, 154 ng/mL), and venous cord serum (median, 156 ng/mL) [80] or in arterial cord plasma levels from mothers who gave birth vaginally (mean, 150 ng/mL) [81]. However, cord plasma TQ10 levels from mothers who had given birth by cesarean section were reported to be lower when receiving general anesthesia (mean, 70 ng/mL) and higher when receiving spinal anesthesia (mean, 240 ng/mL), respectively (Table III) [81].…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Our cord plasma samples being a mixture of arterial and venous cord plasma showed median TQ10 levels of 113 ng/mL and was in excellent agreement with levels found exclusively in venous cord plasma (mean, 112 ng/mL) [50], arterial (median, 154 ng/mL), and venous cord serum (median, 156 ng/mL) [80] or in arterial cord plasma levels from mothers who gave birth vaginally (mean, 150 ng/mL) [81]. However, cord plasma TQ10 levels from mothers who had given birth by cesarean section were reported to be lower when receiving general anesthesia (mean, 70 ng/mL) and higher when receiving spinal anesthesia (mean, 240 ng/mL), respectively (Table III) [81].…”
Section: Discussionmentioning
confidence: 52%
“…However, cord plasma TQ10 levels from mothers who had given birth by cesarean section were reported to be lower when receiving general anesthesia (mean, 70 ng/mL) and higher when receiving spinal anesthesia (mean, 240 ng/mL), respectively (Table III) [81]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, no evidence exists whether the fetus is subject to oxidative stress during labour [28]. Several studies have shown that umbilical arterial blood of newborns delivered vaginally or after emergent caesarean section contains higher levels of oxidation products than the blood of newborns delivered by elective caesarean section [2932]. However, other reports suggest that oxidative stress in the fetal circulation does not depend on the mode of delivery [28].…”
Section: Discussionmentioning
confidence: 99%
“…16 Also, in a placebo-controlled trial, it had been observed that CoQ 10 supplementation during pregnancy reduces the risk of developing preeclampsia in women. 29 Therefore, a decrease in the level of CoQ 10 during pregnancy may be severe for the fetus. A few studies have demonstrated the increased CD4/CD8 ratio 27 and IgG levels on CoQ 10 supplementation.…”
Section: Discussionmentioning
confidence: 99%